Design And Performance Analysis Of Integrated High Gain DC- DC Converter - M.Maheshwari, Dr M. Arounassalame (International Journal of Advanced Science and Technology, 2020)
This paper proposes a novel integrated high gain DC-DC converter. The novel high gain converter is the combination of Quadratic boost (QBC) and SEPIC topologies and the voltage gain of this proposed converter is high when compared to that of the ordinary quadratic boost topology.  The proposed topology uses single power switch and it improves the voltage gain without extreme duty ratio. The proposed novel integrated high gain dc-dc converter reduces the ripples in input current and maintains the constant dc output voltage and hence increases the efficiency. The performance of the proposed high gain converter is compared with quadratic boost converter and SEPIC converter. The simulations have been implemented using MATLAB/ Simulink and the results were reported